Cyber Victimology: Innovative Models and Mechanisms for Protecting Child Victims of Sexual Violence Crimes in the Context of Cybercrime - Guntara, Peter; Harmastuti, Primadia Putri; Putra, Calvin Andika; Liani, Feti (Journal of Law, Politic and Humanities, 2025)
This study was motivated by the complex urgency caused by the prevalence of sexual violence against children in the cyber world. Sexual violence against children leaves victims with deep trauma, anxiety, and social withdrawal. This study uses a normative legal research method with an in-depth literature review approach to analyse the implementation of positive law in Indonesia in protecting child victims of sexual violence in cybercrime, as well as innovations and mechanisms for protecting child victims of sexual violence in cybercrime. As a synthesis and solution, this study projects PELITA Model (Easy, Safe, and Child-Friendly Reporting; Digital Education and Literacy; Integrated Legal, Psychological, and Medical Services; Legal and Digital Forensic Infrastructure; Capable Child Investigators; and Collaborative Law Enforcement Officials) as a comprehensive framework. This model is designed to bridge the gap by synergistically integrating the strengths of formal law and operational innovation, emphasising a victim-centred approach from preventive, repressive, to rehabilitative measures. In conclusion, this study argues that effective protection requires an evolution from a reactive paradigm towards a proactive and adaptive protection system for child victims. PELITA Model can serve as a strategic roadmap for realising holistic protection for child victims of sexual violence in the digital space.